LITERASI INFORMASI UNTUK MENCAPAI KESETARAAN PEREMPUAN: STUDI DENGAN PENDEKATAN FEMINIS LIBERAL PADA PROGRAM “IBU MELI” (IBU MELEK INFORMASI) - Dian Novita Fitriani; Niswa Nabila Sri Bintang Alam; Tri Soesantari (Jurnal IPI (Ikatan Pustakawan Indonesia), 2018)
The purpose of this study is to formulate information literacy skills possessed by IBU MELI and the information literacy skills possessed by IBU MELI are able to achieve equality for women. The method used in this study is a descriptive qualitative research method with a feminist approach. The results of this study found that mothers of IBU MELI program cadres had understood the importance of information and information literacy. They are able to identify their information needs and are able to search from various sources of information, one of which is through collections on the reading corner. From the information literacy held by the mothers of the IBU MELI program cadres, they were able to obtain equality in obtaining information and developing themselves. They are also capable of being fully human by being able to determine their own destiny and solve problems based on various information they have.